Ultrashort pulse laser welding of glasses without optical contacting - Richter, Soren; Zimmermann, Felix; Sutter, Dirk; Budnicki, Aleksander; Tunnermann, Andreas; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
We report on ultrashort pulse induced welding of fused silica without previously optical contacting of the samples. We used a TruMicro 2020 by TRUMPF delivering bursts of intense ultrashort laser pulses with an individual pulse energy of up to 10 μJ, an intraburst pulse separation of 20 ns and a burst repetition rate of 200 kHz. With this setup we could realize a large pool of molten material with a length of up to 450 μm and a diameter of around 160 μm. If the laser focus is placed near the surface of a glass sample the low viscosity of the hot material induces bulging of the surface and ejection of the molten material. This molten material can be used to fill a gap of up to 3 μm between fused silica samples. We also determined the breaking strength with a three-point bending test. The determined maximal value of 73 MPa is equivalent to 85% of the stability of the pristine bulk material.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Femtosecond laser materials processing; Heat accumulation; Laser welding of glass; Optical contacting